Increased Regulatory T Cells Precede the Development of Bronchopulmonary Dysplasia in Preterm Infants - Pagel, Julia; Twisselmann, Nele; Rausch, Tanja K.; Waschina, Silvio; Hartz, Annika; Steinbeis, Magdalena; Olbertz, Jonathan; Nagel, Kathrin; Steinmetz, Alena; Faust, Kirstin; Demmert, Martin; Göpel, Wolfgang; et al. (Frontiers in Immunology, 2020)
Regulatory T cells (Tregs) are important for the ontogenetic control of immune activation and tissue damage in preterm infants. However, the role of Tregs for the development of bronchopulmonary dysplasia (BPD) is yet unclear. The aim of our study was to characterize CD4+ CD25+ forkhead box protein 3 (FoxP3)+ Tregs in peripheral blood of well-phenotyped preterm infants (n =382; 23 + 0 - 36 + 6 weeks of gestational age) with a focus on the first 28 days of life and the clinical endpoint BPD (supplemental oxygen for longer than 28 days of age). In a subgroup of preterm infants, we characterized the immunological phenotype of Tregs (n=23). The suppressive function of Tregs on CD4+CD25- T cells was compared in preterm, term and adult blood. We observed that extreme prematurity was associated with increased Treg frequencies which peaked in the second week of life. Independent of gestational age, increased Treg frequencies were noted to precede the development of BPD. The phenotype of preterm infant Tregs largely differed from adult Tregs and displayed an overall naïve Treg population (CD45RA+/HLA-DR-/Helios+), especially in the first days of life. On day 7 of life, a more activated Treg phenotype pattern (CCR6+, HLA-DR+ and Ki-67+) was observed. Tregs of preterm neonates had a higher immunosuppressive capacity against CD4+CD25- T cells compared to the Treg compartment of term neonates and adults. In conclusion, our data suggest increased frequencies and functions of Tregs in preterm neonates which display a distinct phenotype with dynamic changes in the first weeks of life. Hence, the continued abundance of Tregs may contribute to sustained inflammation preceding the development of BPD. Functional analyses are needed in order to elucidate whether Tregs have potential as future target for diagnostics and therapeutics.